(untitled) (REMUNOM, 2026)
This article presents a bibliographic review on the navigability of the Paciência River, located on São Luís Island, the capital of the state of Maranhão, Brazil. Historically, the river played an important role in the transportation of people and goods, as well as in local fishing and water supply activities. However, over the years, a process of environmental degradation has intensified, mainly caused by rapid and unplanned urbanization, improper disposal of solid waste, discharge of untreated sewage, and illegal occupation of the riverbanks. These factors have directly contributed to the silting of the riverbed, the reduction of navigable depth, and the contamination of the waters, which has compromised navigation even for small vessels. The research is based on scientific articles, dissertations, institutional documents, environmental reports, and historical records that show the evolution of the river’s environmental conditions over time. The study emphasizes the urgent need for coordinated environmental recovery efforts, including sewage treatment, reforestation of riverbanks, urban planning regulations, and eco-friendly dredging practices. Such actions are essential to restore the river’s navigability, ecological balance, and its role as a sustainable urban waterway."